Water Management Zone Mapping on Peatland in Limbung Village Sungai Raya District - Alyaminy, Qishtamy Wahyu; Nusantara, Rossie Wiedya; Krisnohadi, Ari (Universitas Nusantara PGRI Kediri, 2024)
This study focuses on mapping peatland water management zones, which have not been mapped in previous research. These water management zones serve as crucial reference points for the development and implementation of the National Peatland Ecosystem Protection and Management Plan. The research applied various methods, including soil survey, drilling, soil sampling, measuring groundwater level and canal, matching methods, and create a peat water management zone map. Based on research and map overlays, five water management zones were obtained, these zones include Zone I (F2.B1.K1.C2) covering 1.39 ha (11.58%), Zone II (F1.B1.K1.C2) covering 0.82 ha (6. 83%), Zone III (F2.B1.K1.C3) covering 1.93 ha (16.08%), Zone IV (F1.B1.K1.C3) covering 3.86 ha (32.17%) and Zone V (F1.B1.K2.C3) covering 4.00 ha (33.33%). These water management zones will be related to conservation activities to maintain the quality of soil and water on peatlands. Peatland restoration management activities in Zone I can be accomplished by canal blocking and maximum planting patterns, in Zone II by canal filling and maximum planting patterns, in Zone III by canal blocking and enrichment plants, in Zone IV by canal backfilling and maximum planting patterns, and in Zone V by canal backfilling and deep wells.